Simulation of capacitively coupled RF discharge in argon - Lisovskiy, V.; Dudin, S.; Shakhnazarian, A.; Platonov, P.; Yegorenkov, V. (Problems of Atomic Science and Technology, 2023)
In this work, the axial profiles of the density of electrons and positive ions, the mean electron energy, the electric field strength, and the potential were obtained, both on average over the period and in dynamics. It was shown that argon discharges are dominated by ionization by electrons that gained energy by stochastic heating during the expansion of near-electrode sheaths. This ionization occurs in two pulses during one RF period. At low RF voltage between the electrodes, the role of Ohmic heating of electrons in the electric field in a quasi-neutral plasma increases, but the contribution of stochastic heating remains dominant. The time-averaged plasma potential was found to increase non-linearly with the RF voltage between the electrodes Urf. It is shown that at low Urf values (when the RF voltage approaches the discharge extinction curve), the average potential Φ can reach Urf due to the axial redistribution of the instantaneous potential in the gap between Отримано осьові профілі густини електронів та позитивних іонів, середньої енергії електронів, напруженості електричного поля та потенціалу як у середньому за період, так й їхню динаміку. Показано, що в розряді в аргоні переважає іонізація електронами, які набули енергії під час стохастичного нагріву при розши ренні приелектродних шарів. Ця іонізація відбувається двома імпульсами протягом одного ВЧ-періоду. При низькій ВЧ-напрузі між електродами зростає роль омічного нагріву електронів у електричному полі в квазінейтральній плазмі, але внесок стохастичного нагріву залишається домінуючим. З’ясовано, що середній за часом потенціал плазми Φ нелінійно зростає з ВЧ-напругою Urf між електродами. Показано, що при низьких значеннях Urf (при наближенні ВЧ-напругою до кривої згасання розряду) середній потенціал Φ може досягати Urf завдяки осьовому перерозподілу миттєвого потенціалу в проміжку між електродами.